2016
DOI: 10.1186/s12884-016-0824-0
|View full text |Cite
|
Sign up to set email alerts
|

Women’s preferences and mode of delivery in public and private hospitals: a prospective cohort study

Abstract: BackgroundRates of caesarean section have steadily increased in most middle- and high-income countries over the last few decades without medical justification. Maternal request is one of the frequently cited non-medical factors contributing to this trend. The objectives of this study were to assess pregnant women’s preferences regarding mode of delivery and to compare actual caesarean section rates in the public and private sectors.MethodsA prospective cohort study was conducted in two public and three private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
72
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 26 publications
3
72
0
3
Order By: Relevance
“…Of a sample of low-risk, nulliparous, private-sector Argentine women preferring VD in their third trimester, 11% had a documented scheduled CS, 13% of which had medical indications. 25 Of a sample of private-sector Brazilian women preferring VD during their third trimester, 34% delivered via scheduled CS. 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of a sample of low-risk, nulliparous, private-sector Argentine women preferring VD in their third trimester, 11% had a documented scheduled CS, 13% of which had medical indications. 25 Of a sample of private-sector Brazilian women preferring VD during their third trimester, 34% delivered via scheduled CS. 34 …”
Section: Discussionmentioning
confidence: 99%
“…We are grateful to Dr Agustina Mazzoni (IECS) for sharing survey instruments and other materials used in her study. 25 We could not have done this study without the collaboration and dedication of the Feasibility of ‘Mode of Delivery Trial’ Study Group .…”
mentioning
confidence: 99%
“…Other sources point to the role of supplier-side demand induction behavior [27, 28]. From a consumer perspective, some authors have suggested that women request to have an elective CSD in the absence of clinical indications [29–32]. However, McCourt et al’s critical review [33] found that women’s preference for CSD varied only from 0.3 to 14%.…”
Section: Introductionmentioning
confidence: 99%
“…'nın 13 yapmış olduğu bir çalışmada yaş ve eğitim durumu arttıkça kadınların sezaryen doğuma eğilimlerinin arttığı gösterilmişken çalışma-mızda yaş ile birlikte sezaryen doğuma eğilim olduğu görülmekle birlikte eğitim durumu ile doğum tercihleri arasında bir ilişki belirlenmedi. İleri maternal yaş ile sezaryen doğuma eğilimin artmasının nedeni, kadınların daha fazla sosyal yaşamın içine girmesiyle birlikte çocuk sahibi olmanın geciktirilmesi, dolayısı ile daha ileri yaşlardaki anne adaylarının doğumun daha planlı ve kontrollü hale getirme isteği olabilir.…”
Section: Discussionunclassified